Clearance rate of two commercially important bivalves feeding on pseudo-nitzschia species (Bacillariophyceae) - Tan, Toh Hii (Universiti Malaysia Sarawak, UNIMAS, 2009)
The chain-forming pennate diatom, Pseudo-nitzschia is a cosmopolitan diatom. Contamination of domoic acid (DA), derived from several toxic species of Pseudo-nitzschia in filtered feeding bivalves, has subsequently caused seafood poisoning which is commonly known as amnesic shellfish poisoning (ASP). In this study, a feeding experiment was carried out to determine the clearance rates (CR) of two commercial bivalves, blood cockles, Anadara granosa and benthic clams, Polymesoda expansa feeding on Pseudo-nitzschia species. Mass clonal culture of Pseudo-nitzschia sp. strain PnMt43 from Muara Tebas was used as prey in this experiment. The bivalves were fed with different initial cell density ranging from 100 to 5000 cell mL-1. Subsamples were taken half-hourly for a period of six hours for cell counts. Our results showed two distinct clearance responses between the two bivalves (P = 0.0020). P. expansa had the higher CR with 7.316 cell gram-1 mL-1 day than A.granosa with 0.389 cell gram-1 mL-1. The half-saturation concentrations (K) for A. granosa and P. expansa were 955 and 437 cell mL-1, respectively. The higher clearance rate of P. expansa indicates the tendency to accumulate higher level of toxin during a Pseudo-nitzschia bloom. However, P. expansa with higher CR has lower K due to the difference in consumption pattern. Simulation of toxin kinetic of the two bivalves was not able to be conducted due to the absence of toxic Pseudo-nitzschia strains. Further studies on feeding responses and toxin accumulation-depuration rates are important to understand the mechanism of toxin kinetic of DA in these two commercially important bivalves.